2021
DOI: 10.2196/31064
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability, Engagement, and Exploratory Outcomes of an Emotional Well-being App: Mixed Methods Preliminary Evaluation and Descriptive Analysis

Abstract: You selected:'No' -Are the participants in your study randomised to different groups? 'No' -Does your study protocol demand changing treatment/ patient care from accepted standards for any of the patients involved? 'No' -Are your findings going to be generalisable? Your study would NOT be considered Research by the NHS.You may still need other approvals.Researchers requiring further advice (e.g. those not confident with the outcome of this tool) should contact their R&D office or sponsor in the first instance,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…The app developed in this study provides direction and guidance on how to report symptoms, events, and daily emotional states and provides an easy display to integrate these various inputs and share insights with health care providers. Unlike existing mobile apps with several views on multiple interfaces [ 46 - 48 ], this app provides a single view of all symptoms, events, and emotions consolidated on 1 page which aims to improve usability, efficiency, and satisfaction among users. The design also allows an effective presentation of daily reports in a comprehensive and easy-to-understand manner.…”
Section: Discussionmentioning
confidence: 99%
“…The app developed in this study provides direction and guidance on how to report symptoms, events, and daily emotional states and provides an easy display to integrate these various inputs and share insights with health care providers. Unlike existing mobile apps with several views on multiple interfaces [ 46 - 48 ], this app provides a single view of all symptoms, events, and emotions consolidated on 1 page which aims to improve usability, efficiency, and satisfaction among users. The design also allows an effective presentation of daily reports in a comprehensive and easy-to-understand manner.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies (5/19, 26%) did not find any differences in baseline mental well-being levels between participants who did and did not drop out [27,29,32,35,36]. However, 1 study found that participants with lower mental well-being and higher levels of anxiety, depression, and distress were more likely to drop out [30], whereas another study found that participants with higher mental well-being and lower levels of anxiety, depression, and distress were more likely to drop out [31].…”
Section: Study Dropout and Attritionmentioning
confidence: 94%
“…There were a range of findings across studies on the association between participants' demographic characteristics and dropout. One study found that male participants were more likely to drop out [36], whereas others (2/19, 11%) found no difference [27,31]. Some studies (2/19, 11%) found that participants who remained in the study were older [35,38], although other studies (2/19, 11%) did not find this effect [31,36].…”
Section: Study Dropout and Attritionmentioning
confidence: 99%
See 2 more Smart Citations